Statin Use and Influenza Vaccine Effectiveness in Persons >65 Years of Age, Taiwan - Tsai, Lung-Wen (Emerg Infect Dis, 2020)
Debates on whether statin use reduces the effectiveness of influenza vaccines against critical illness and death among persons >65 years of age continue. We conducted a study of 9,427,392 persons >65 years of age who did and did not receive influenza vaccinations during 12 consecutive influenza seasons, 2000–01 through 2011–12. Using data from Taiwan’s National Health Insurance Research Database, we performed propensity score-matching to compare vaccinated persons with unvaccinated controls. After propensity score-matching, the vaccinated group had lower risks for in-hospital death from influenza and pneumonia and for hospitalization for pneumonia and influenza, circulatory conditions, and critical illnesses compared with the unvaccinated group. We stratified the 2 groups by statin use and analyzed data by interaction analysis and saw no statistically significant difference. We found that influenza vaccine effectively reduced risks for hospitalization and death in persons >65 years of age, regardless of statin use.